Anisotropic hopping conduction in spin-coated PEDOT: PSS thin films - Mantovani Nardes, Alexandre; Kemerink, Martijn; Janssen, René A. J. (Physical review. B, Condensed matter and materials physics, 2007)
The charge transport in spin-coated poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) has been investigated as a function of temperature and electric field. Both the magnitude and the transport mechanism are found to be strongly anisotropic. This striking behavior is quantitatively explained in terms of a morphological model in which flattened, quasimetallic PEDOT-rich grains are organized in horizontal layers that are separated by continuous insulating PSS lamellas. In this model, the in-plane conductivity is described by three-dimensional variable range hopping between ∼25nm sized PEDOT-rich particles separated by subnanometer PSS barriers, while the out-of-plane conductivity is described by nearest-neighbor hopping between more widely spaced molecular sites. These length scales are supported by previously reported scanning probe measurements.